Key factors to evaluate the impact of bilingual programs: Employability, mobility and intercultural awareness - Gómez Parra, María Elena; Huertas-Abril, Cristina Aránzazu; Espejo-Mohedano, Roberto (Porta Linguarum An International Journal of Foreign Language Teaching and Learning, 2021)
The importance of bilingual education is widely debated in the scientific world; it represents an opportunity for millions of international students in the 21st century, endorsed with varied benefits, including cognitive, neurolinguistic, socio-cultural, academic or labor, among others. The main objective of this work is to evaluate the impact of bilingual education on students who graduated from bilingual programs by measuring three key factors (employability, mobility and intercultural awareness), and comparing the results with those from a group of students who graduated from non-bilingual programs. A factorial analysis was carried out to reduce the size of the original set of variables from 11 to 3, thus constituting a model of scientific efficiency. Finally, this paper shows a statistical evaluation of the real effects that bilingual programs have achieved since implementation, concluding that the three main factors identified here allow the scientific evaluation of the success of bilingual programs.